1998
DOI: 10.1023/a:1004431104540
|View full text |Cite
|
Sign up to set email alerts
|

Fracture and fatigue performance of textile commingled yarn composites

Abstract: The response to mechanical loads of commingled warp knitted and woven glass fibre reinforced polyethylene terephthalate (GF/PET) laminates has been characterised. The mechanical properties of the two materials were determined under tension, in-plane shear and flexure. The flexural fatigue properties were determined for the woven laminates by means of three point bending tests with a loading ratio of R=0.1 at stress levels of 50-90% of the ultimate static strength. The Mode I, Mode II and mixed mode (Mode I:II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…However, the inter-laminar stresses within laminated materials are localised at interfaces due to the strong discreteness in the material properties. This localisation of stress can lead to delamination and crack propagation [4][5][6]. To eliminate the stress localisation, a proper continuous gradient is required to smooth the property transition 3 through the thickness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the inter-laminar stresses within laminated materials are localised at interfaces due to the strong discreteness in the material properties. This localisation of stress can lead to delamination and crack propagation [4][5][6]. To eliminate the stress localisation, a proper continuous gradient is required to smooth the property transition 3 through the thickness.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that, for a particular density, a foam is most efficient at absorbing the kinetic energy of an impact over a limited range of 5 stress, after which the stress rises rapidly with little corresponding increase in absorbed energy. By means of a functionally graded foam, it may be possible to combine a large range of densities to improve the energy absorbing efficiency over a wider range of stress levels.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to traditional thermoset matrix composites the crack initiation and propagation toughness is higher for these materials. Models for predicting mixed mode delamination in prepreg and textile composites have been developed by the author and are discussed in detail elsewhere [5,6].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…For this reason, the woven laminates were also subjected to flexural fatigue loading [5]. A decrease in failure load to about 60% of the maximum static flexural strength was observed after 10 6 load cycles.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…[1,2] The big advantage of graded foams is the improved mechanical stability of the material under low energy impact, while still performing nearly as well as their uniform counterpart under high energy conditions. [19][20][21] One possibility to generate a density gradient without lamination is reaction injection molding. Other potential applications for functionally graded foams are interfacial tissue engineering, [7][8][9] especially for bone implants, [10][11][12] (micro) filtration, [13][14][15] as well as construction.…”
mentioning
confidence: 99%